2019
DOI: 10.1111/mmi.14240
|View full text |Cite
|
Sign up to set email alerts
|

Colistin heteroresistance in Enterobacter cloacae is regulated by PhoPQ‐dependent 4‐amino‐4‐deoxy‐l‐arabinose addition to lipid A

Abstract: The Enterobacter cloacae complex (ECC) consists of closely related bacteria commonly associated with the human microbiota. ECC are increasingly isolated from healthcare-associated infections, demonstrating that these Enterobacteriaceae are emerging nosocomial pathogens. ECC can rapidly acquire multidrug resistance to conventional antibiotics. Cationic antimicrobial peptides (CAMPs) have served as therapeutic alternatives because they target the highly conserved lipid A component of the Gram-negative outer memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 57 publications
7
75
0
Order By: Relevance
“…However, there have been few studies of lipid A structure with respect to colistin heteroresistance. Research has demonstrated that E. cloacae lipid A is modified with L-Ara4N to induce colistin heteroresistance (14). Here we further analyzed the lipid A profiles to uncover the LPS-modified features in heteroresistant isolates and to determine the association between resistant and heteroresistant strains.…”
Section: Colistin (Hetero)resistance In Pseudomonas Aeruginosamentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been few studies of lipid A structure with respect to colistin heteroresistance. Research has demonstrated that E. cloacae lipid A is modified with L-Ara4N to induce colistin heteroresistance (14). Here we further analyzed the lipid A profiles to uncover the LPS-modified features in heteroresistant isolates and to determine the association between resistant and heteroresistant strains.…”
Section: Colistin (Hetero)resistance In Pseudomonas Aeruginosamentioning
confidence: 99%
“…Colistin homogeneous resistance develops mainly due to mutations in the twocomponent regulatory systems (TCSs) (PhoPQ and PmrAB) (10,11). Specific mutations trigger constitutive upregulation of the pmrHFIJKLM-ugd operon, which leads to the covalent attachment of 4-amino-4-deoxy-L-arabinose (L-Ara4N) to the lipid A component of the outer membrane lipopolysaccharide (LPS) (12)(13)(14). Recently, ParRS, CprRS, and ColRS TCSs have also been found to play a role in colistin homogeneous resistance in P. aeruginosa (15)(16)(17).…”
mentioning
confidence: 99%
“…This ultimately leads to treatment failure and death of the infected mice (Band et al, 2016). It was shown that these heteroresistant E. cloacae cells survive colistin treatment by modifying the lipopolysaccharide component of their outer membrane (Band et al, 2016;Kang et al, 2019). This modification is dependent on the histidine kinase PhoQ, which is part of the PhoP-PhoQ two-component system (Band et al, 2016;Groisman, 2001).…”
Section: Phenotypic and Genetic Origins Of Heteroresistancementioning
confidence: 99%
“…This modification is dependent on the histidine kinase PhoQ, which is part of the PhoP-PhoQ two-component system (Band et al, 2016;Groisman, 2001). This system is activated by limiting Mg 2+ concentrations (Groisman, 2001), conditions that were shown to induce E. cloacae heteroresistance to colistin (Kang et al, 2019). Because it is currently unknown how the E. cloacae PhoP-PhoQ system is regulated, it remains unclear how its activation leads to resistance in only a part of the population.…”
Section: Phenotypic and Genetic Origins Of Heteroresistancementioning
confidence: 99%
“…For example, in the E. cloacae complex, a response-regulator complex senses change in cation concentrations and activates transcription of lipid A modification enzymes, causing a temporary increase in resistance to colistin. 112 In Enterobacteriaceae, transcription of efflux pumps is often controlled by cellular sensing of antibiotics. 113 In gram-positive bacteria, inducible macrolide resistance is regulated transcriptionally and post-transcriptionally, often upregulating programs to protect the ribosome or pump out the macrolide.…”
Section: Adaptive Resistance: Physiology Engenders Resistancementioning
confidence: 99%